1995
DOI: 10.1111/j.1464-5491.1995.tb00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Patency, Limb Salvage and Survival in Diabetic and Non‐diabetic Patients Undergoing Infrainguinal Bypass Surgery

Abstract: In 92 diabetic and 175 non-diabetic patients undergoing 336 femoropopliteal or femorodistal bypass procedures, 1- and 3-year cumulative life-table patency, limb salvage, and survival rates were comparatively analysed. The peroperative mortality rate was significantly higher in diabetic patients (5% compared to 1.4%, p < 0.001). The cumulative graft patency rates were 61% at 12 months and 46% at 36 months in diabetic patients compared to 64 and 52% in non-diabetic patients. Significantly better patency rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
2
28
1
1
Order By: Relevance
“…These benefits however, are associated with a high perioperative mortality of 18% in our patients, which was a reflection of their advanced coronary and other concomitant diseases. Nevertheless, survival in diabetic patients appears to be limited [4, 13], and survival in patients with ESRD is even more limited [8]. In a series with similar characteristics to ours, Whittemore et al [14] also reported a 30-day mortality of 11%.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…These benefits however, are associated with a high perioperative mortality of 18% in our patients, which was a reflection of their advanced coronary and other concomitant diseases. Nevertheless, survival in diabetic patients appears to be limited [4, 13], and survival in patients with ESRD is even more limited [8]. In a series with similar characteristics to ours, Whittemore et al [14] also reported a 30-day mortality of 11%.…”
Section: Discussionsupporting
confidence: 51%
“…However, patency rates in patients with ESRD continue to be significantly lower than rates in patients with normal renal function [10,11,12]. On the other hand, it is now generally accepted that the patency rate for infrainguinal revascularization is similar in diabetic and non-diabetic patients; however, higher late mortality and limb loss have been reported in diabetic compared to non-diabetic patients [4,5,6]. The present study confirms that the presence of diabetes mellitus and ESRD are associated with good primary and secondary patency rates, and most important, with a well-accepted limb salvage rate of 65% in the first year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiography is required to define the anatomy and the outcome of traditional techniques for revascularization in the form of distal bypass that seems to be comparative in patients with and without diabetes. 6 The Bypass versus Angioplasty in Severe Ischaemia of the Leg (BASIL) randomized trial compared surgery and endovascular techniques and concluded that for severe leg ischemia, a patient with a life expectancy of >2 years should be offered bypass surgery in preference but offered EVT if life expectancy was <2 years. 7 This reflects the fact that bypass is more likely to result in longer term patency and limb salvage.…”
mentioning
confidence: 99%
“…Another study assessed the 1-and 3-year cumulative life-table patency, limb salvage and survival rates [27]. The cumulative graft patency rates were 61% at 12 months and 46% at 36 months in diabetic patients compared with 64% and 52% in non-diabetic patients [27].…”
Section: Diabetes Mellitusmentioning
confidence: 99%